Development of Islamic Education Learning Methodology Based on Learning Theory Approaches Behaviorisme - Bahrin, Sitirahma; Mujahidin, Endin; Lisnawati, Santi (-, 2025)
This study aims to examine the relevance of applying behaviorism theory in developing Islamic Religious Education (PAI) learning methodology. The method used is library research through a descriptive-analytical approach. The results show that behaviorism theory can be integrated into PAI learning through systematic steps, starting from material analysis, formulating learning objectives, determining strategies, to evaluation, analyzing evaluation results, improving learning, and refining methods. However, this theory has limitations because it does not highlight the spiritual and inner aspects, which are the core of Islamic education. Therefore, the integration of behaviorism theory in PAI learning needs to be aligned with Islamic values so that the goals of Islamic education can be achieved.